2022
DOI: 10.3389/fmed.2021.773724
|View full text |Cite
|
Sign up to set email alerts
|

Increased CDCA2 Level Was Related to Poor Prognosis in Hepatocellular Carcinoma and Associated With Up-Regulation of Immune Checkpoints

Abstract: BackgroundCell division cycle-associated protein 2 (CDCA2) is a member of cell cycle-related proteins. CDCA2 plays a role in the regulation of protein phosphatase 1(PP1) γ-dependent DNA damage response (DDR) and H3 phosphorylation. CDCA2 promotes the tumorigenesis and development of several types of cancers by promoting the proliferation of tumor cells. However, the relationship between CDCA2 expression and the clinicopathological characteristics of hepatocellular carcinoma (HCC) is unknown.MethodsGene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The potential use of this aptamer in HCC immunotherapy was previously explored 38 . It was also found that the upregulation of immune checkpoint CD274 could increase the expression of cell division cycle-associated protein 2 (CDCA2) and predict the poor prognosis of HCC 39 . We found that ACTG1, E2F3, RASSF3, and WDR76 in the ceRNA network are closely related to the immune checkpoints, suggesting that the ceRNA network regulates the immune escape of HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The potential use of this aptamer in HCC immunotherapy was previously explored 38 . It was also found that the upregulation of immune checkpoint CD274 could increase the expression of cell division cycle-associated protein 2 (CDCA2) and predict the poor prognosis of HCC 39 . We found that ACTG1, E2F3, RASSF3, and WDR76 in the ceRNA network are closely related to the immune checkpoints, suggesting that the ceRNA network regulates the immune escape of HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to reports, which revealed that overexpression of CDCA2 is a common event in lung, prostate, and oral cancers, Tang et al reported that CDCA2 was increased in HCC as well based on analyses of data from TCGA [ 17 ]. Furthermore, they suggested that CDCA2 had a high diagnostic power and was associated with poor survival for HCC [ 17 ]. On the basis of these reports, we investigated the effects of CDCA2 on the malignant behaviors of HCC cells using biological experiments in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, activation of AKT–mTOR pathway contributes to the progression of lung cancer, breast cancer, endometrial cancer, and HCC [ 27 30 ]. Using gene set enrichment analysis, Tang et al demonstrated that CDCA2 may be involved in mTOR pathway [ 17 ]. Consistently, by biological experiments, we discovered that overexpression of CDCA2 triggered the increasing of phosphorylation of mTOR and AKT in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations